Hydro-edaphic Properties of Woodland Habitat of Nilgiris Biosphere Reserve - Tamilnadu and Karnataka and their Relationship with its Flora - Part I - Singh, J. N.; Chaturvedi, S. P. (Indian Forester, 2011)
The study was aimed at to investigate the hydro-edaphic properties of Woodland habitat of Nilgiris Biosphere Reserve (NBR) and their possible relationship with its flora. Mechanically, the soils within two states are quite sound and are capable to support the taxa of mighty dimension and lofty height. There are six textural classes of soils in Tamil Nadu - NBR and seven in Karnataka. Due to high presence of clays contents in the majority of the soil types within NBR - Tamilnadu make the soil texturally superior over their counterpart in Karnataka. Data on physico-chemical characteristics of the soil irrespective of state demonstrate the superiority of their acquired characteristics over inherent. The inherent characteristics of the soil in both states of NBR are heavily loaded with silica, sesquioxides and iron oxides which are not congenial to the proper growth and development of flora of the area. It is further illustrated that one delicate but stable equilibrium is functioning among soilvegetation and climate of the region, which is remarkably tilted towards degradation in both states. Soils as whole within two states are feebly acidic to moderately acidic in reaction, possess sufficient reserve of energy materials within Tamil Nadu, but in Karnataka, they are noticeably bereft. Their other physico-chemical characteristics such as water holding capacity, porosity, available nitrogen, phosphorus and cation exchange capacity are relatively superior in Tamil Nadu than Karnataka. The waters of Tamil Nadu are categorized as C1 S1 class, whereas, water of Karnataka come under C2 S1 category and as such they have direct bearing on flora and fauna of the area.